2009
DOI: 10.1128/jb.00601-09
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar Formation in C-Ring-Defective Mutants by Overproduction of FliI, the ATPase Specific for Flagellar Type III Secretion

Abstract: The flagellar cytoplasmic ring (C ring), which consists of three proteins, FliG, FliM, and FliN, is located on the cytoplasmic side of the flagellum. The C ring is a multifunctional structure necessary for flagellar protein secretion, torque generation, and switching of the rotational direction of the motor. The deletion of any one of the fliG, fliM, and fliN genes results in a Fla ؊ phenotype. Here, we show that the overproduction of the flagellum-specific ATPase FliI overcomes the inability of basal bodies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…On the other hand, the EscQ protein, which is proposed to be the major component of the sorting platform (48), appeared to be more important for secretion, although it could be bypassed by overproduction of the EspA translocator. The nonessential nature of the equivalent flagellar components (FliM, FliN, FliH, and FliG) has already been reported (60,61,81), unraveling a common mechanism of action of this cytoplasmic complex in type III secretion machineries. Importantly, it has been shown that the assembly of the core of the injectisome (basal body and export apparatus) is not affected in the absence of the cytoplasmic components (SctQ, SctL, and SctK) (33,48,52,69), so it is possible that this primordial core is sufficient to drive protein secretion, providing a surplus of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the EscQ protein, which is proposed to be the major component of the sorting platform (48), appeared to be more important for secretion, although it could be bypassed by overproduction of the EspA translocator. The nonessential nature of the equivalent flagellar components (FliM, FliN, FliH, and FliG) has already been reported (60,61,81), unraveling a common mechanism of action of this cytoplasmic complex in type III secretion machineries. Importantly, it has been shown that the assembly of the core of the injectisome (basal body and export apparatus) is not affected in the absence of the cytoplasmic components (SctQ, SctL, and SctK) (33,48,52,69), so it is possible that this primordial core is sufficient to drive protein secretion, providing a surplus of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The FliH defect is bypassed by the overexpression of FliI or extragenic suppressor mutations in FlhA or FlhB (25). In addition, the requirement of the C ring for the flagellar export process is overcome by the overexpression of FliI (18,23) or upregulation of the expression of the FlhD-FlhC complex, which acts as the master regulator in the flagellar gene expression system (8). These observations suggest that the interaction of FliH EN with FliN increases the local concentration of FliI around the export gate and that the interaction of FliH EN with FlhA allows the effective docking of FliI to the FlhA-FlhB platform for efficient and rapid protein export under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The FliH-FliI complex binds to the C ring through a specific interaction of FliH with a C ring protein, FliN (12,23,37,41). The overexpression of FliI alone or the FliH-FliI complex significantly enhances the reduced secretion activity of the fliN null mutant, suggesting that the FliH-FliN interaction increases the local concentration of the FliH-FliI-FliJ-chaperone-substrate complex around the export gate, thereby allowing the complex to efficiently associate with the export gate (8,18,23,37). Then, a specific association between the FliH-FliI-FliJ complex and the FlhA C -FlhB C docking platform on the export gate induces the formation of the FliH X -FliI 6 -FliJ ring complex onto the platform, thereby facilitating the initial entry of the substrates into the export gate (35).…”
mentioning
confidence: 99%
“…Notably, the phenotype of C ring mutants can be suppressed by enhanced levels of the ATPase FliI or the master regulator FlhDC. It was therefore concluded that the C ring per se is not essential for flagellum formation (160,280).…”
Section: The Predicted Cytoplasmic C Ring Of the T3s System Is A Potementioning
confidence: 99%